2007
DOI: 10.1016/j.joca.2007.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Membrane type-1 matrix metalloproteinase is induced following cyclic compression of in vitro grown bovine chondrocytes

Abstract: These data suggest that cyclic compression of chondrocytes in vitro upregulates MT1-MMP via ERK1/2 dependent activation of Egr-1 binding. Delineation of the regulatory pathways activated by mechanical stimulation will further our understating of the mechanisms influencing tissue remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 52 publications
(58 reference statements)
2
22
0
Order By: Relevance
“…Our study showed that bovine chondrocytes are motile although their role in cartilage repair and integration in this model is unknown. Previous studies in our laboratory have highlighted the importance of matrix remodeling, mediated in part by the protease MT1-MMP, in improving tissue formation [9,10]. Given the role of MT1-MMP in cell migration [11,37], it is possible this metalloprotease is involved in chondrocyte motility; however, further study is required to confirm this.…”
Section: Discussionmentioning
confidence: 95%
“…Our study showed that bovine chondrocytes are motile although their role in cartilage repair and integration in this model is unknown. Previous studies in our laboratory have highlighted the importance of matrix remodeling, mediated in part by the protease MT1-MMP, in improving tissue formation [9,10]. Given the role of MT1-MMP in cell migration [11,37], it is possible this metalloprotease is involved in chondrocyte motility; however, further study is required to confirm this.…”
Section: Discussionmentioning
confidence: 95%
“…Grb2 has been known to play a positive role in receptor tyrosine kinase signaling [24, 25], and the association of Grb2 and Shc/FAK is upstream to the activation of MAPK, which is an important signaling pathway leading to the proliferation and matrix synthesis of chondrocytes when exposed to periodic mechanical stress [26, 27]. We therefore hypothesized that the effect of Grb2 in mechanical signal transduction in chondrocytes may be related to the stimulation of MAPK pathway.…”
Section: Resultsmentioning
confidence: 99%
“…2000; Ohtani et al 2004), but also regulate the cells' adhesion and migration through participating in the transcription activation of CCN1 (Grote et al 2004) and MT1-MMP (De Croos et al 2007). These results provided the first evidence that TF decoy strategies might be used to prevent and cure diseases (Morishita et al 1998).…”
Section: Discussionmentioning
confidence: 99%